Application Of Feldspar Filler On Curing Characteristics And Physical Properties Of Elastomeric Materials - Mohd Din, Shamin Aida (Universiti Sains Malaysia, 2022)
Carbon black (CB) and silica are fillers that have been widely used worldwide in the tire industry. The use of feldspar in tire manufacturing is one alternative to conventional fillers due to its cost effectiveness and sustainability. In this work, a compound of styrene-butadiene rubber (SBR) filled with carbon black (CB) and feldspar has been conducted to determine the ability of feldspar as a reinforcement filler in tire tread applications. This work has also involved investigating the effects of using different types of sulfur vulcanization systems such as conventional vulcanization systems (CV), efficient vulcanization systems (EV), and semi-efficient vulcanization systems (semi-EV) for both control and hybrid compounds. For the control compound, 40 parts per hundred rubber (pphr) of CB, Silica and Feldspar were used and for the hybrid compound, the ratio between CB and filler was 30:10, 20:20 and 10:30. Based on the results, the control compound from semi-EV system has short scorch and cure time for the SBR-Feldspar compound. For the hybrid compound, SBR-CB-Feldspar with the high CB loading, 30 pphr has already improved the curing characteristics and physical properties of the elastomer material such as tensile strength, hardness, rebound resilience, and abrasion resistance. However, feldspar is still not on par with silica as a reinforcement filler. For hybrid filler systems with various types of elastomer materials, such as SMR-L, EPDM, NBR, and CR, the behavior of these rubbers is different in terms of curing characteristics and physical properties when compared to SBR compounds due to the original nature of the rubber involved. Feldspar may be considered as a semi-reinforcing filler and acts as an extender and softener in elastomer compounds.